Systematic Review With Meta‐Analysis of Patient‐Centered Outcomes, Comparing International Guideline–Recommended Enteral Protein Delivery With Usual Care. Issue 4 (15th October 2019) - Fetterplace, Kate; Gill, Benjamin M. T.; Chapple, Lee‐anne S.; Presneill, Jeffrey J.; MacIsaac, Christopher; Deane, Adam M.
Abstract: Background: International guidelines recommend that protein be administered enterally to critically ill patients at doses between 1.2 and 2 g/kg per day Observational data indicate that patients frequently receive less protein. The aim of this systematic review was to evaluate patient‐centered outcomes with guideline‐recommended enteral protein compared with usual care. Methods: A systematic review was performed of randomized controlled trials including critically ill adult patients provided predominately enteral nutrition with mean protein at ≥1.2 g/kg per day (intervention) and <1.2 g/kg per day (comparator). Random‐effects models were applied for outcomes reported in ≥3 trials. Results: Of 1375 abstracts, 69 full‐text articles were reviewed, and 6 trials meet the inclusion criteria, including 511 patients. The intervention group received a mean (SD) of 1.3 (0.08) g/kg per day, and the comparator group received 0.75 (0.15) g/kg per day protein. Insufficient data were available for meta‐analyses on the primary outcome (muscle mass or strength). According to our meta‐analyses, mortality at 28 days (5 studies) (risk ratio 0.92 [95% Cl 0.63–1.35], P = .66) and the durations of intensive care unit (6 studies) and hospital admission (4 studies) were similar between the intervention and comparator, with some uncertainty due to sample sizes and heterogeneity. Conclusion: There are insufficient data to conclude whether protein provision within the current international guideline recommendations improves outcomes. In a limited dataset, enteral protein intakes near the lower level of current recommendations do not appear to reduce admission duration or mortality when compared with usual care in critically ill.